2004
DOI: 10.1097/00129334-200406000-00012
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Telemedicine in the Management of Diabetes-Related Foot Ulceration: A Pilot Study

Abstract: These data appear to support the effectiveness of real-time interactive telemedicine consultation in the management of diabetes-related forefoot ulceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(111 citation statements)
references
References 19 publications
2
109
0
Order By: Relevance
“…A nonrandomized study by Wilbright et al (20) showed no significant difference between the telemedical group and the control group in time to complete healing of diabetic ulcers. The present results also demonstrate no difference with respect to healing and amputation and thus suggest that telemedicine is at least as good as standard clinic visits.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A nonrandomized study by Wilbright et al (20) showed no significant difference between the telemedical group and the control group in time to complete healing of diabetic ulcers. The present results also demonstrate no difference with respect to healing and amputation and thus suggest that telemedicine is at least as good as standard clinic visits.…”
Section: Discussionmentioning
confidence: 94%
“…A number of randomized controlled trials have investigated the potential and feasibility of telemedicine in ulcer care (14)(15)(16)(17)(18)(19), but only two of these present clinical outcomes (15,18). Only one nonrandomized study focused specifically on diabetic foot ulcers and telemedicine (20). The aim of the present study was to compare telemedical and standard outpatient monitoring in the care of patients with diabetic foot ulcers with a focus on ulcer healing and amputation.…”
mentioning
confidence: 99%
“…Preliminary results of the studies by Wilbright et al 3 and Debray et al 4 suggest that clinical images together with additional data from the patient's history are usually sufficient for a correct diagnosis and appropriate therapy of diabetes-related foot ulcers and wounds in elderly patients.…”
Section: For Editorial Comment See Page 1581mentioning
confidence: 99%
“…Because providers in some communities may not have ready access to specialists, they may consider consultation via electronic or telephonic arrangements (sometimes referred to as telemedicine) [71,72]. Although using high-resolution optical equipment may be optimal [73], even standard or video telephones have allowed expert consultation from a distance [74].…”
Section: Evidence Summarymentioning
confidence: 99%